Political violence in Judaism, Christianity, and Islam from holy war to modern terror - Fine, Jonathan (Rowman & Littlefield, 2015)
A unique comparative study of religious political violence across Judaism, Islam, and Christianity, this text features many international case studies from the Crusades to the Arab Spring.